The Value of a Comparative Approach to Understand the Complex Interplay between Microbiota and Host Immunity - Morella, Norma M.; Koskella, Britt (Frontiers in Immunology, 2017)
The eukaryote immune system evolved and continues to evolve within a microbial world, and as such is critically shaped by - and in some cases even reliant upon - the presence of host-associated microbial species. There are clear examples of adaptations that allow the host to simultaneously tolerate and/or promote growth of symbiotic microbiota whilst protecting itself against pathogens, but the relationship between immunity and the microbiome reaches far beyond simple recognition and includes complex cross-talk between host and microbe as well as direct microbiome-mediated protection against pathogens. Here, we present a broad but brief overview of how the microbiome is controlled by and interacts with diverse immune systems, with the goal of identifying questions that can be better addressed by taking a comparative approach across plants and animals and different types of immunity. As two key examples of such an approach, we focus on data examining the importance of early exposure on microbiome tolerance and immune system development and function, and the importance of transmission among hosts in shaping the potential coevolution between, and long-term stability of, host – microbiome associations. Then, by comparing existing evidence across short-lived plants, mouse model systems and humans, and insects, we highlight areas of microbiome research that are strong in some systems and absent in others with the hope of guiding future research that will allow for broad scale comparisons moving forward. We argue that such an approach will not only help with identification of generalities in host-microbiome immune interactions but also improve our understanding of the role of the microbiome in host health.